2020
DOI: 10.3389/fimmu.2020.01795
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Processes May Involve in the IgG4-RD Pathogenesis: An Integrative Study via Proteomic and Transcriptomic Analysis

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a newly defined disease entity, while the exact pathogenesis is still not clear. Identifying the characters of IgG4-RD in proteomic and transcriptomic aspects will be critical to investigate the potential pathogenic mechanisms of IgG4-RD. We performed proteomic analysis realized with iTRAQ technique for serum samples from eight treatment-naive IgG4-RD patients and eight healthy volunteers, and tissue samples from two IgG4-RD patients and two non-IgG4-RD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…Notably, IGLV2-11 and IGLV7-43 were involved in the Fc-gamma receptor-signaling pathway and were increased in Mikulicz group compared with Head and neck group in saliva ( Figure 3C ). Interestingly, “Fc-gamma receptor signaling pathway” was also detected in IgG4-RD tissue in our previous paper ( 11 ), which may suggest a potential role in the pathogenesis of IgG4-RD Mikulicz group.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Notably, IGLV2-11 and IGLV7-43 were involved in the Fc-gamma receptor-signaling pathway and were increased in Mikulicz group compared with Head and neck group in saliva ( Figure 3C ). Interestingly, “Fc-gamma receptor signaling pathway” was also detected in IgG4-RD tissue in our previous paper ( 11 ), which may suggest a potential role in the pathogenesis of IgG4-RD Mikulicz group.…”
Section: Resultsmentioning
confidence: 54%
“…In this paper, we compared the DEPs identified in our previously published proteomic plasma data (11) with the screened DEPs between IgG4-RD patients and HCs in this study, we found a number of DEPs were overlapped (Table S5). Thus, we will examine the potential of these proteins in the differential diagnosis of IgG4-RD using a larger number of IgG4-RD samples in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Four recent articles reviewing the pathogenesis of IgG4-RD were not mentioning platelets in any context. 9,35,36,38 Another significant research was performed by Cai et al 13 by Tsuboi et al) from GEO data repository for validation of their findings. 13 In both serum and tissue samples of IgG4-RD patients, Cai et al documented several platelet related terms (i.e., "Platelet activation", "Platelet degranulation", "Platelet aggregation", "Blood coagulation", "Hemostasis", and "Coagulation") to be enriched among many other titles.…”
Section: Discussionmentioning
confidence: 97%
“…The Gene Expression Omnibus (GEO) database is a large repository, integrated with a series of high-throughput microarray and next-generation sequence functional genomic datasets, and is free for global researchers [12]. Up to now, GEO database have helped numerous researchers to identify key mechanisms and hub targets of cardiovascular diseases, tumors, and other diseases [13][14][15]. The regulation of a pathway often involves several genes, and there are coexpression relationships among these genes.…”
Section: Introductionmentioning
confidence: 99%